A bioinformatics approach for mass spectrometry data processing: Applications to proteomics and small molecule analysis. Issue 2 (2002) - Sonderegger Sonderegger, Martin Martin; Staniszewski Staniszewski, Kristin Kristin; Meyers Meyers, Andrew Andrew; Siuzdak Siuzdak, Gary Gary
Abstract : We have developed a web‒based software system, JULIAN, that simplifies the process of relaying mass spectral information for chemists, protein chemists, biochemists and all others performing mass spectrometry experiments through a centralized mass spectrometry laboratory. JULIAN allows for relative ease in submitting compound information as well as instant access to analysis results from any networked computer equipped with a web browser. Compound information is centralized in a Microsoft Access database and results are available in Adobe's portable document format (PDF) from an NT4 server. This gives researchers the ability to easily obtain data and allows the analysts in the mass spectrometry lab to browse analysis results when assisting researchers with their inquiries. Due to this web‒based design JULIAN is independent of the mass spectrometers' hardware and operating system. Approximately seven hundred on‒site and off‒site users have utilized JULIAN transmitting over 40, 000 analyses. The conversion from paper to electronic mass spectrometry data processing has enabled our Center to receive compound information, perform analysis, and relay the results four times faster than required previously.